2020
DOI: 10.1111/exd.14074
|View full text |Cite
|
Sign up to set email alerts
|

Growth factor concentrations in platelet‐rich plasma for androgenetic alopecia: An intra‐subject, randomized, blinded, placebo‐controlled, pilot study

Abstract: Background Platelet‐rich plasma (PRP), processed from autologous peripheral blood, is used to treat androgenetic alopecia (AGA). Objective To determine the efficacy of PRP for hair growth promotion in AGA patients in a randomized, blinded, placebo‐controlled, pilot clinical trial (NCT02074943). Methods The efficacy of an 8 week, five session, PRP treatment course was determined by measuring hair density and hair caliber changes in 10 AGA affected patients. For each PRP sample, the concentrations of selected gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…The variable levels of secretion by platelets highlight the existence of inherent heterogeneity between individual patients. Our findings are consistent with a recent study [ 25 ] which measured physiologic GF concentrations in inactivated PRP used for treatment of AGA patients, indicating that clinical improvements to therapy may also be variable. Therefore, the inherent heterogeneity in gene expression and secretion in platelets among patients may be dependent on genetic and environmental factors driving epigenetic changes in megakaryocyte.…”
Section: Discussionsupporting
confidence: 92%
“…The variable levels of secretion by platelets highlight the existence of inherent heterogeneity between individual patients. Our findings are consistent with a recent study [ 25 ] which measured physiologic GF concentrations in inactivated PRP used for treatment of AGA patients, indicating that clinical improvements to therapy may also be variable. Therefore, the inherent heterogeneity in gene expression and secretion in platelets among patients may be dependent on genetic and environmental factors driving epigenetic changes in megakaryocyte.…”
Section: Discussionsupporting
confidence: 92%
“…Another source of heterogeneity is likely the wide range of growth factor concentrations present in PRP preparations between individuals. Supporting this, a recent study by Siah et al 50 quantified growth factor concentrations in PRP for each participant and found significant variability. They discovered a correlation between hair density increase and the concentrations of glial cell line‐derived neurotrophic factor (GDNF) and vascular endothelial growth factor (VEGF).…”
Section: Discussionmentioning
confidence: 64%
“… 15–17 Activated platelets in PRP release numerous growth factors and cytokines from their alpha granules, including platelet-derived endothelial growth factor (PDGF), transforming growth factor β (TGF-β), fibroblast growth factor-2 (FGF-2), vascular endothelial growth factor (VEGF), epidermal growth factor (EGF), insulin-like growth factor-1 (IGF-1), glial cell line–derived neurotrophic factor (GDNF), which play a major role in stimulating hair growth through cell proliferation, differentiation and angiogenesis. 18–22 GDNF can stimulate cell proliferation and protect hair follicle from premature catagen transition. 23 , 24 VEGF play a major role as a potent hair growth stimulator via an angiogenesis induction.…”
Section: Classification Of Platelet Rich Plasmamentioning
confidence: 99%